LIPID PEROXIDATION PROCESS ACTIVITY IN MICROSOMAL FRACTION OF RATS’ LIVER DURING IMPACT OF OLIGOESTERS OF POLYATOMIC ALCOHOL - Бондарева, А.В.; Стеценко, С.О. (World of Medicine and Biology, 2016)
Significant intensity of xenobiotics impact on person’s and animal’s organism defines topicality of research to find out new approaches in order to compensate abnormality of functions. Oligoesters of polyatomic alcohol present wide spread xenobiotics, which are characterized by significant synthesis volume, wide use and impact on person’s health. It has been proved major number of xenobiotics causes oxidative metabolism in microsomes of hepatocytes, generation of active forms of oxygen can cause side effect. This question of OEF-LP impact has not studied yet, so it is necessary to study its biological action and also the development of ways of its correction. Samples of OEF-LP 502 (polyoxypropylene glycol) and 503 (polyoxypropylene triol) were used in this work with defined physical and chemical peculiarities. Experiments were done on sexually mature rats of Wistar with body weight (180-220) gram. They were exposed to peroral coarse with probe by water solution of compounds daily and once time during 45 days in doses 1/10 and 1/100 LD50. Investigation of indices was done in dynamics on the 15th, 30th, 45th, 60th days after experiment’s start. Secretion of microsomal fraction of rats’ liver was done by differential centrifugation. Activity of systems of enzymatic-induced (NADPH-dependent) and nonenzymatic (ascorbate-dependent) lipid peroxidation in suspension of microsomes of rats’ liver has been determined by the speed of accumulation of malondialdehyde (MDA) in reaction with thiobarbituric acid after prooxidants intake. Qualitative evaluation of products of OEF destruction in rats’ urine on the 60th day was done due to independent method of chromatography.